The Effect of Parabiotic Reuterin on the Expression of Genes Involved in Candida albicans Biofilm Formation: An Ex vivo Study - Riad, Anastasya Muna; Widyarman, Armelia Sari (Journal of Dentistry Indonesia, 2021)
Candida albicans has a number of properties, including resistance to various antimicrobial agents, which allow it to survive in the root canals. Lactobacillus reuteri plays a role in maintaining oral health through interactions with the oral microbiome. L. reuteri has potential as a preventive and therapeutic agent against inflammatory diseases. Objective: The aim of this study was to investigate the effect of irrigation with a reuterin-containing solution on BCR1, ACE2, EFG1, and TEC1 gene expression in C. albicans root canal biofilms. Methods: L. reuteri was cultured in MRS broth and incubated anaerobically for 24 hours at 37°C. C. albicans was cultured in Sabouraud dextrose broth at 37°C for 48 hours. A total of 24 single-rooted premolar teeth were standardized and inoculated with C. albicans before irrigation with 50 μg/mL reuterin as a single, independent variable (Indonesian strain), 50 μg/mL reuterin Prodentis (a strain combination of L. reuteri DSM 17938 and L. reuteri ATCC PTA 5289), 2.5% sodium hypochlorite as positive control, and saline as negative control. A real-time quantitative polymerase chain reaction (RT-qPCR) assay was used to detect the expression of BCR1, ACE2, EFG1, and TEC1 in C. albicans root canal biofilms. Results: Reuterin significantly reduced the expression of BCR1 and ACE2 genes, which play a role in C. albicans biofilm formation, at the biofilm maturation stage (P < 0.05). Reuterin also affected the expression of the EFG1 and TEC1 genes, although the effect was not significant. Conclusion: A reuterin isolate of L. reuteri exhibits antibiofilm activity against the expression of C. albicans genes involved in biofilm formation. Reuterin has potential as an irrigation agent in the treatment of root canals. Further research is needed to shed light on the effectiveness of reuterin against the expression of genes that play important roles in the formation of C. albicans biofilms.